Estonia’s digital diplomacy: Nordic interoperability and the challenges of cross-border e-governance - Alex Hardy (Internet Policy Review)
Estonia has long been held as a leading example of e-Governance. Estonia’s ubiquitous e-Governance is enabled by the X-Road, an open-source data exchange layer that allows the secure exchange of data. This paper explores the X-Road integration between Estonia, Finland, Iceland, the Faroe Islands and the Åland Islands. Having been originally pioneered and implemented by Estonia and developed by the Estonian Information System Authority (RIA), X-Road is increasingly attractive to other nations drawn to the digital services it can enable. This paper argues that the cross-border implementation of the X-road, pioneered by Estonia, is a form of digital diplomacy – an opportunity to extend influence and shape e-norms among geopolitically like-minded partners.